Mining, corporate social responsibility and communities in Limpopo Province: the case study of Mogalakwena Local Municipality - Chipa, Maboloka Jonas (University of the Free State, 2021)
The current study scrutinised the positive and negative effects of the communities closer to the Anglo-American Platinum Mine (AAPM) in Limpopo Province, Mogalakwena Local Municipality. A qualitative approach was applied to this study, and respondents were selected through crucial informants. The researcher also used a semi-structured interview method. Currently, the mining policies introduced in South Africa, such as the Mineral and Petroleum Resource Act No 28 of 2002 (MPRDA), as well as other mining sector policies. The study also discussed the National Environmental Management Act 107 of 1998 and emphasised that the mining right cannot be issued without the Environmental Impact Assessment Study (EIA). NEMA was ammended during 2014 where the South African Government proposed that the mining companies should put finances aside for the rehabilitation of the land. Broad-Based Socio-Economic Empowerment (BBSE) was introduced to redress the issue of the past. The MPRDA also redressed and developed the mining sector by introducing the Social Labour Plan (SLP). The SLP guidelines also clarify the mining industry about the development and improvement of the local economy. Human resource development primarily focuses on increasing mining skills. The mining charter also introduced the procurement plan divided into three levels: consumables, capital goods, and services. Research revealed that the Ga-Mapela communities were significantly provided with social infrastructures by the AAMP. The AAMP employed the local community who have matric certificates with mathematics and physical sciences. Direct traditional community leaders from different Ga-Mapela villager’s asked the AAMP to develop a gravel main road. However, they were referred to government. Ga-Mapela communities also experience the adverse effects of AAMP mining activities. Those negative effects include noise and dust during blasting, disturbing the community, and cracking houses. The natural resources were also affected, especially the local river water and groundwater. The community noted the changing taste of groundwater, while the animals died after drinking the river water. Mountains and graveyards are negatively affected by AAMP mining activities. The AAMP employed a few communities due to requirements. When the youth realised the AAMP has a prerequisite before hiring, they mobilised themselves and protested. During the expansion, the AAMP informed paramount chiefs and community forums, excluding direct local traditional leaders, which caused the protests. The study recommends that the AAMP a create friendship with local communities, reduce the health hazard and protect the environment and biodiversity. Government and AAMP should work together in the development of the local economy and generate employment for the local community. However, intensive research should be conducted by the AAMP before implementing any development to the community.
Dissertation (MDS (Development Studies))--University of the Free State, 2021
Keywords: Anglo-American platinum mine; Mining policies - South Africa; Broad-Based Socio-Economic Empowerment (BBSE); Mining - Corporate - Social responsibility